Features predicting the level of food security of Russian regions in the light of the geopolitical changes - V. S. Balabanov; M. N. Dudin; N. V. Ljasnikov (Путеводитель предпринимателя)
The article deals with the concept of food security predict regions of Russia, studied the system of natural balances of agricultural raw materials and by-products. The theme of this article is highly relevant in the light of the geopolitical changes, so the correctness and accuracy of the prediction offood supply and food security in the regions is new and one of the most important managerial tasks in the modern world.